Characterization of pet ownership in Buenos Aires city, Argentina - Tortosa, Analía (2017)
The aim of this study was to determine demographic and ownership pet characteristics, motivations, attitudes and behaviours of the human population raising or not raising pets, especially dogs in Buenos Aires city. A prevalence explanatory social study was designed in two areas of the city with different socio-economic structure. A survey was conducted in 357 households in San Cristóbal (group 1) and in 169 households in Barrio Mitre (group 2). A high proportion of animals per household in both areas was observed. Per capita canine ownership rates significantly differed which can be attributed to different socio-economic status. Differences in the proportion of canine female, small size and purebred with variation in mortality, birth and survival rates indicate that pet populations tend to be reflection of social and living conditions of the human population. It was observed that sterilization can be used for reproductive control or to meet needs of close coexistence in urban areas. Mostly, canines are incorporated through gift, purchase or collection in public places. Adoption was not considered an option to get a dog. Cognitive maps of canine ownership were performed to characterize qualitatively and quantitatively the link between animals and their holders and proved to be a novel way to analyse the interrelationship of variables.